2010
DOI: 10.3109/02813432.2010.518407
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Framingham and SCORE cardiovascular risk prediction functions in a non-diabetic population of a Spanish health care centre: a validation study

Abstract: Objective. To analyse the 10-year performance of the original Framingham coronary risk function and of the SCORE cardiovascular death risk function in a non-diabetic population of 40-65 years of age served by a Spanish healthcare centre. Also, to estimate the percentage of patients who are candidates for antihypertensive and lipid-lowering therapy. Design. Longitudinal, observational study of a retrospective cohort followed up for 10 years. Setting. Primary care health centre. Patients. A total of 608 non-diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…One Framingham model has previously been validated in six prospective, ethnically diverse cohorts 7 and was shown to have reasonable calibration overall, but prior data specifically for the ATP-III model are sparse. Other, primarily European, investigators have also reported that various versions of Framingham models over-predict CHD incidence, 8,9,35,36 Since clinicians in practice cannot re-calibrate a score for an individual patient, population calibration is essential.…”
Section: Discussionmentioning
confidence: 99%
“…One Framingham model has previously been validated in six prospective, ethnically diverse cohorts 7 and was shown to have reasonable calibration overall, but prior data specifically for the ATP-III model are sparse. Other, primarily European, investigators have also reported that various versions of Framingham models over-predict CHD incidence, 8,9,35,36 Since clinicians in practice cannot re-calibrate a score for an individual patient, population calibration is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Despite similarities in estimated outcome, results are conflicting in precision and accuracy. Although some claim the Framingham 10‐year risk calculator to estimate close to the actual observed risk, others state that the Framingham risk model overestimates the risk of CVD, or underestimate it in young women. Previous studies claimed the calculated 10‐ and 30‐years CV risk, based on the Framingham risk calculator to be raised in former PE patients compared to controls .…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly due to the decline in cardiovascular mortality. This overestimation was reported in many European countries [18-21] but not in all [22,23]. The significant effect of medication on the ΔSCORE probably reflects the direct effect of lipid levels and blood pressure on the parameters included in the calculation of SCORE.…”
Section: Discussionmentioning
confidence: 90%